Primary plant nutrients modulate the reactive oxygen species metabolism and mitigate the impact of cold stress in overseeded perennial ryegrass - Ihtisham, Muhammad; Hasanuzzaman, Mirza; El-Sappah, Ahmed H.; Zaman, Fawad; Khan, Nawab; Raza, Ali; Sarraf, Mohammad; Khan, Shamshad; Abbas, Manzar; Hassan, Muhammad Jawad; Li, Jia; Zhao, Xianming; et al. (Frontiers in Plant Science, 2023)
Overseeded perennial ryegrass (Lolium perenne L.) turf on dormant bermudagrass (Cynodon dactylon Pers. L) in transitional climatic zones (TCZ) experience a severe reduction in its growth due to cold stress. Primary plant nutrients play an important role in the cold stress tolerance of plants. To better understand the cold stress tolerance of overseeded perennial ryegrass under TCZ, a three-factor and five-level central composite rotatable design (CCRD) with a regression model was used to study the interactive effects of nitrogen (N), phosphorus (P), and potassium (K) fertilization on lipid peroxidation, electrolyte leakage, ROS production, and their detoxification by the photosynthetic pigments, enzymatic and non-enzymatic antioxidants. The study demonstrated substantial effects of N, P, and K fertilization on reactive oxygen species (ROS) production and their detoxification through enzymatic and non-enzymatic pathways in overseeded perennial ryegrass under cold stress. Our results demonstrated that the cold stress significantly enhanced malondialdehyde, electrolyte leakage, and hydrogen peroxide contents, while simultaneously decreasing ROS-scavenging enzymes, antioxidants, and photosynthetic pigments in overseeded perennial ryegrass. However, N, P, and K application mitigated cold stress-provoked adversities by enhancing soluble protein, superoxide dismutase, peroxide dismutase, catalase, and proline contents as compared to the control conditions. Moreover, N, P, and, K application enhanced chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids in overseeded perennial ryegrass under cold stress as compared to the control treatments. Collectively, this 2−years study indicated that N, P, and K fertilization mitigated cold stress by activating enzymatic and non-enzymatic antioxidants defense systems, thereby concluding that efficient nutrient management is the key to enhanced cold stress tolerance of overseeded perennial ryegrass in a transitional climate. These findings revealed that turfgrass management will not only rely on breeding new varieties but also on the development of nutrient management strategies for coping cold stress.